Recaptured Africans : surviving slave ships, detention, and dislocation in the final years of the slave trade - Fett, Sharla M. (The University of North Carolina Press, 2017)
"In the years just before the Civil War, during the most intensive phase of American slave-trade suppression, the U.S. Navy seized roughly 2,000 enslaved Africans from illegal slave ships and brought them into temporary camps at Key West and Charleston. In this study, Sharla Fett reconstructs the social world of these "recaptives" and recounts the relationships they built to survive the holds of slave ships, American detention camps, and, ultimately, a second transatlantic voyage to Liberia"-- Provided by publisher
Keywords: Enslaved persons -- United States -- Social conditions -- 19th century.; Enslaved persons -- United States -- History -- 19th century.; Slave trade -- United States -- History -- 19th century.; Esclaves -- États-Unis -- Conditions sociales -- 19e siècle.; Esclaves -- États-Unis -- Histoire -- 19e siècle.; Traite des esclaves -- États-Unis -- Histoire -- 19e siècle.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; HISTORY -- Africa -- West.; Slave trade; Enslaved persons; Enslaved persons -- Social conditions; United States; 1800-1899; Electronic books.; History